SEM analysis of internal adaptation of adhesive restorations after contamination with saliva - Duarte Jr., Sillas [UNESP]; Lolato, Antonio Luiz; Buainain de Freitas, Cláudia Regina [UNESP]; Dinelli, Welingtom [UNESP] (My University, 2005)
Purpose: This study tested the null hypothesis that different treatments of saliva-contaminated substrate would not affect microgap formation at the dentin walls of bonded restorations. Materials and Methods: Forty freshly extracted human molars received standardized Class V preparations on buccal and lingual surfaces. The specimens were assigned to four experimental groups (n = 20): [G1] no contamination (control group), [G2] saliva contamination (10 s) after etching followed by 5 s air stream; [G3] saliva contamination after etching and rinsed for 10 s; and [G4] re-etching for 10 s after saliva contamination. All specimens were restored with a one-bottle adhesive (Single Bond, 3M ESPE) and microhybrid composite resin (Filtek Z250, 3M ESPE) according to the manufacturer's instructions. The specimens were thermocycled, sectioned through the center of the restoration, and then processed for SEM. Microgaps were measured at the axial wall at 1500X magnification. The data were submitted to Kruskal-Wallis nonparametric statistical analysis at p < 0.05. Results: The data revealed that different groups resulted in a statistically significant difference (p < 0.01) in gap formation. Air drying [G2] and rinsing [G3] the saliva-contaminated dentin resulted in similar microgap values (p > 0.05). However, re-etching the dentin after saliva contamination [G4] increased microgap formation (p < 0.05) when compared with the groups G1 and G2. Although air drying and rinsing produced results comparable to noncontaminated dentin, the presence of microgaps was not completely eliminated. Conclusion: Contaminated saliva did not prevent hybrid layer formation; however, it did reduce the adaptation of the restorative material to bonded surfaces.
Keywords: Adhesive microgap; Contamination; Saliva; adhesive agent; contamination; controlled study; dental etching; dentin; human; Kruskal Wallis test; molar tooth; saliva; scanning electron microscopy; statistical analysis; statistical significance; Acid Etching, Dental; Air; Bisphenol A-Glycidyl Methacrylate; Composite Resins; Dental Bonding; Dental Stress Analysis; Dentin; Dentin Permeability; Dentin-Bonding Agents; Humans; Marginal Adaptation (Dentistry); Microscopy, Electron, Scanning; Molar; Phase Transition; Resin Cements; Statistics, Nonparametric; Water